Hybrid Professionalism in Platformized Journalism: Personal Branding, Professional Identity, and Career Attractiveness - Hasanah, Khuswatun; Indah, Sika Nur; Dewanti, Ida Susi (RSF Conference Series: Business, Management and Social Sciences, 2025)
Platformization is reshaping role performance, boundary work, and newsroom temporalities, influencing how Communication students imagine their professional selves and careers. This study investigates whether acceptance of personal branding undermines or can coexist with professional identity, how branding relates to the appeal of a journalism career, how students perceive digital-era workload, and how fears of AI align with readiness to use it. We conducted a cross-sectional, multi-campus survey in Yogyakarta with N = 150 communication students across diploma and bachelor's tracks, using Likert-type items grouped into three domains and combined into composite indices. The data were then analyzed using descriptive statistics, Pearson correlations, and independent-samples t-tests by practice exposure in reporting and internships. The results indicate a hybrid form of professionalism, where the acceptance of personal branding does not erode professional identity and is positively associated with career attractiveness. Students anticipate high digital workloads, with pressure higher among those who have completed internships or reporting tasks. They show pragmatic ambivalence toward AI, expressing concern yet remaining moderately willing to use assistive tools under editorial governance. By jointly examining branding, professional identity, career attractiveness, AI perceptions, and practice-related workload in a Global South context, this study extends theoretical debates beyond Euro-American settings and highlights curricular implications, including the incorporation of brand-as-journalist ethics, AI oversight, and authentic workload simulations.